Optimalisasi Rute Menggunakan Algoritma Dijkstra dan Greedy: Sebuah Pendekatan Komparatif - Jelita, Felisa; Fallo, Diana; Miru, Yoseph Gayus (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to analyze and compare the effectiveness of three algorithms that are often used in finding the shortest path, namely the Dijkstra Algorithm, the Greedy Algorithm, and the A* Algorithm. The problem of finding the shortest path is one of the basic challenges in the field of computer science, especially in applications such as navigation systems, logistics, and digital mapping. This study was conducted by conducting a literature study of more than 20 trusted scientific references published between 2015 and 2024. The results of the analysis show that the Dijkstra algorithm provides a high level of accuracy and guarantees optimal results, although it requires more time and memory. The Greedy algorithm excels in time efficiency and simplicity, but does not guarantee an optimal solution. The A* algorithm combines the strengths of Dijkstra and Greedy through a heuristic approach that promises efficiency and accuracy at the same time. This study concludes that the selection of algorithms should be adjusted to the context of their application and that the A* algorithm can be an effective compromise solution. These findings are expected to provide theoretical and practical contributions in the development of intelligent and adaptive route optimization systems.Keywords: Dijkstra algorithm, Greedy algorithm, shortest path, route optimization, algorithm comparison